Eksplorasi Pembelajaran berbasis Budaya Sekep (Filosofi Profil Pelajar Pancasila di SDN Pangarangan III Sumenep) - Akhmad Said Hidayat; Moh. Rifqi Rahman (Sekolah Tinggi Agama Islam YPBWI Surabaya, 2022)
Madura has a diverse culture with a plethora of philosophical ideals. Sekolah Dasar Negeri (SDN) Pangarangan III Sumenep Madura elaborates on sekep, a Madurese tradition that eventually formed an abbreviation for Se Kobasa (The Almighty), Kecca' (critical thinking), and Panolong (mutual cooperation). The purpose of this study was to describe and explore the use of the three aspects of the acronym sekep in the learning process. This is a case study. Data for this study were acquired through observation and interviews. Miles et al. analytical processes, such as condensing data, presenting data, and drawing conclusions, were employed in data analysis. Dimensions for creating important indicators in learning include Se Kobasa, Kecca', and Panolong. Se Kobasa indicators include having faith and piety to Allah SWT and having high morals; Kecca' indicators include being creative, critical, communicative, and collaborative; and Panolong indicators include mutual collaboration. These three aspects were implemented as Se Kobasa at the start of learning, Kecca' in the midst of learning, and Panolong at the conclusion of learning. In this study, the linearity of sekep with the profile of Pancasila students was discussed.